Low‐Frequency Induced Polarization of Porous Media Undergoing Freezing: Preliminary Observations and Modeling. Issue 5 (15th May 2019) - Coperey, A.; Revil, A.; Abdulsamad, F.; Stutz, B.; Duvillard, P. A.; Ravanel, L.
Abstract: We investigate the thermal dependence of the complex conductivity of nine porous materials in the temperature range +20 °C to −10 or −15 °C. The selected samples include three soils, two granites, three clay‐sands mixes, and one graphitic tight sandstone. A total of 12 experiments is conducted with one sample tested at three different salinities. Our goal is to use this database to extend the dynamic Stern layer polarization model in freezing conditions. We observe two polarization mechanisms, one associated with the effect of the change in the liquid water content and its salinity upon the polarization of the porous material. A second mechanism, at higher frequencies (>10 Hz), is likely associated with the polarization of ice. At low frequencies and above the freezing point, the in‐phase and quadrature conductivities depend on temperature in a predictable way. This dependence is due to the dependence of the mobility of the charge carriers with temperature. Below the freezing point, the in‐phase and quadrature conductivity follow a brutal decay with temperature. This dependence is modeled through an exponential freezing curve function. We were also able to determine how the (apparent) formation factor and surface conductivity change with temperature and water content below the freezing point. Our model is able to replicate the data at low frequencies and predicts correctly the fact that the ratio between the normalized chargeability and the surface conductivity is independent of the water content and temperature and equals a well‐defined dimensionless number R. Key Points: Electrical conductivity and normalized chargeability of frozen rocks are described in a consistent way The model is tested against a new database made on nine core samples in the temperature range +20 degrees Celsius and ‐15 degrees Celsius A good agreement is obtained between the model and the experimental data